A novel pathogen assay based on the loop-mediated isothermal amplification using retroreflective Janus particles as a nonspectroscopic signaling probe - Chun, Hyeong Jin; Kim, Seongok; Kim, Ka Ram; Jeong, Kwan Young; Yoon, Hyunjin; Yoon, Hyun C. (22nd International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2018, 2018)
Loop-mediated isothermal amplification (LAMP) is a novel gene amplification method. The amplified LAMP product can be visualized via fluorescence signal or turbidity, which is generated from the fluorescent intercalating dyes or white magnesium pyrophosphate precipitate, respectively. However, these detection methods can only judge the presence or absence of target gene. Thus, quantification of target gene concentration is difficult. To overcome this limitation, we introduced a novel biosensing platform based on the LAMP assay using retroreflective Janus particle which is used as an optical probe. Using the developed sensing system, quantitative analysis of the invA in Salmonella Typhimurium are successfully accomplished.
Keywords: Janus particles; Loop mediated isothermal amplifications; Molecular diagnostics; Optical bio-sensing; Salmonella typhimurium; Loop-mediated isothermal amplification; Molecular diagnostic; Optical biosensing system; Retroreflective Janus particles; Salmonella Typhimurium